Analysis of The Impact of ICT Into Condominium Management. Scientific Literature Review 2015 - 2020 - Dolly B. ASTO AGUILAR; Jamil G. BELEN BARRETO; Liset S. RODRIGUEZ BACA (Communications of International Proceedings, 2021)
The global advancement of technology and communications means that more and more companies, turn their manual process into automated process, allowing greater speed and efficiency in their operations, reducing the use of traditional materials such as office and this managing to be eco-efficient companies (Kutnjak, Pihiri and Furjan, 2019). That is why the analysis is carried out, to expose the impact Information and Communication Technologies into the condominium management. This research includes a study of documents published between 2015 and 2020, which were extracted from different academic sources such as IEEE, International Journal of Innovation in Enterprise, ScienceDirect, Scopus, ResearchGate, Taylor & Francis Online, and Springer Link; being a total of 50 articles, manifesting new advances related to the subject studied. There results of the research show the benefits of incorporating ICT into condominiums, both in the automation of condominium management activities, internal communication and eco-efficiency. It is concluded that ICT in condominium management provides benefits as long as the real estate project requires it.
Keywords: Condominium management; ITC; Communication; Eco-Efficiency